Spatially controlled two-dimensional quantum heterostructures. Issue 5 (4th May 2023) - Kim, Gwangwoo; Song, Seunguk; Jariwala, Deep
Abstract : Two-dimensional (2D) heterostructures have recently attracted interest as candidate materials for classical optoelectronics and in quantum information technology. Despite significant research, realizing deterministic, in-plane quantum confinement in synthetic 2D heterostructures at the nanoscale remains challenging. In this brief overview, we summarize recent advances in approaches for the growth of spatially controllable 2D quantum heterostructures. These growth methods enable the achievement of various 2D lateral/vertical heterostructures with controlled positions and dimensions while minimizing defects across the heterointerfaces. In addition, we provide an outlook on the future direction of developments and applications of 2D quantum-confined heterostructures. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Two-dimensional (2D) heterostructures have been investigated for optoelectronics and quantum engineering. This review provides critical analysis and perspective into the realization of spatially controlled 2D quantum heterostructures and their applications.